Inter- and Intraobserver Variability in the Assessment of Brain Arteriovenous Malformation Angioarchitecture and Endovascular Treatment Results - Iancu-Gontard, D. (AJNR Am J Neuroradiol, 2007)
BACKGROUND AND PURPOSE: Several angiographic features of brain arteriovenous malformations (BAVMs) have been associated with an increased risk of hemorrhage. However, interpretation of these features may not be consistent between observers. We conducted a study to determine inter- and intraobserver agreement of various angioarchitectural characteristics of BAVM. MATERIALS AND METHODS: Two experienced interventional neuroradiologists independently reviewed pre- and post-endovascular treatment angiograms from 50 consecutive patients. Axial CT and/or MR images before treatment were included. We collected the following data: Spetzler-Martin grades, number of involved arterial territories, associated aneurysms by location (circle of Willis, feeding artery, intranidal, and venous), and nidus reduction after endovascular treatment (<33%, 33%–66%, and >66%). The reviewers were compared with each other, and 1 was compared with himself after a 3-month interval. Measures of agreement were performed by using the kappa statistic (κ) for nominal data and the weighted κ for ordinal data. RESULTS: Inter- and intraobserver agreement were higher for assessment of the Spetzler-Martin grade (weighted κ = 0.70/0.75) and nidus size reduction after endovascular treatment (κ = 0.74/0.77). Inter- and intraobserver agreement were inferior for findings concerning feeding artery aneurysms (κ = 0.19/0.36), intranidal aneurysms (κ = 0.34/0.35), and venous aneurysms (κ = 0.50/0.67). CONCLUSION: Angiographic characteristics of BAVMs considered as risk factors for hemorrhage, such as aneurysms, are not reliably detected on global angiograms between different observers. In contrast, the Spetzler-Martin grading system and angiographic results of endovascular treatment can be used with high observer agreement.